G-DRG-Version 2016: Auswirkungen auf unser Fachgebiet = G-DRG-Version 2016 : its impact on our specialty - Mende, Hendrik Marius; Olenik, Daniela; Schleppers, Alexander (Anästhesiologie & Intensivmedizin, 2016)
The DRG-2016 catalogue contains only moderate adjustments of DRGs and additional fees. There are now 1,220 DRGs and 179 additional charges available. Priorities in the development of classificatory were particular areas of intensive care, extreme costs, treatment of children and the reduction of conflict potential in the encoding. As measured by the changes during the past few years only sparse innovations result from this year’s DRG-catalogue for our specialty. In order to be able to represent our area of expertise in the DRG system according to our performances in 2015 as well, the changes of this year’s system must be taken into our documentary routine.